Рhonetics vs Phonology - Gurkalo, V.; Kushnir, A. S.; Гуркало, В.; Кушнір, А. С. (Вінницька міська друкарня, 2022)
The article actualizes the problem of the essence of the concepts of phonetics and phonology and describes different approaches to the interpretation of the mentioned phenomena. It also identifies the main differences between these concepts and, based on the analyzed definitions, highlights their own view on the difference between the terms phonetics and phonology.
Фонетика проти фонології
Keywords: phonetics; phonology; speech sounds; syllables; intonation and prosody